2021
DOI: 10.3389/fphys.2021.704599
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Neuromodulation for Mass Vagus Nerve Stimulation: Insights From SOS COVID-19 a Multicentric, Randomized, Controlled, Double-Blind French Pilot Study

Abstract: Importance: An exacerbated inflammatory response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is believed to be one of the major causes of the morbidity and mortality of the coronavirus disease 2019 (COVID-19). Neuromodulation therapy, based on vagus nerve stimulation, was recently hypothesized to control both the SARS-CoV-2 replication and the ensuing inflammation likely through the inhibition of the nuclear factor kappa-light-chain-enhancer of activated B cells pathway and could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Three different articles [ 80 , 81 , 82 ], using three different non-invasive VNS techniques, started randomized controlled trials in 2020 in France (SOS-COVID-19) and Spain (SAVIOR I), and in 2021 in Austria, respectively, enrolling stage 3 hospitalized COVID-19 patients requiring oxygen supply. Rangon et al [ 80 ] treated the patients with four semi-permanent needles on the conchae of both outer ears (without concurrent electrical stimulation) to stimulate the auricular branch of the vagus nerve, once within the first 3 days after admission. Tornero el al.…”
Section: Discussion: Novel Therapies Targeting Vagus Nerve Stimulatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Three different articles [ 80 , 81 , 82 ], using three different non-invasive VNS techniques, started randomized controlled trials in 2020 in France (SOS-COVID-19) and Spain (SAVIOR I), and in 2021 in Austria, respectively, enrolling stage 3 hospitalized COVID-19 patients requiring oxygen supply. Rangon et al [ 80 ] treated the patients with four semi-permanent needles on the conchae of both outer ears (without concurrent electrical stimulation) to stimulate the auricular branch of the vagus nerve, once within the first 3 days after admission. Tornero el al.…”
Section: Discussion: Novel Therapies Targeting Vagus Nerve Stimulatio...mentioning
confidence: 99%
“…The device delivered intermittent electrical stimulation (3 h on/3 h off) with a 1 Hz frequency, 0.5–0.9 mA peak current (1.5 mA maximum), 1 ms pulse width, and 3.8 V fixed amplitude. No study at all was able to show a significant improvement in the clinical outcomes of the COVID-19-positive inpatients (clinical status assessed either too early (14 [ 80 ] and 5 days [ 81 ] after the first VNS session), or not at all [ 82 ]), but a good tolerance of the neuromodulation treatments was confirmed. Interestingly, two studies reported a significant improvement in the biological inflammation status of the patients (regarding C-reactive protein and procalcitonin levels [ 81 ]; or C-reactive protein, TNF alpha, DDIMER, and IL-10 levels [ 82 ]).…”
Section: Discussion: Novel Therapies Targeting Vagus Nerve Stimulatio...mentioning
confidence: 99%
“…A French study is assessing auricular nerve stimulation via four percutaneously placed leads on each tragus and is being compared to sham (no needle placement; NCT04341415). Enrollment has been halted due to a low case load ( 142 ).…”
Section: Recent Covid-19 Trialsmentioning
confidence: 99%
“…VNS application extends beyond neurological diseases: a growing body of clinical evidence from human patients indicates its suitability for treatment of chronic heart failure ( 90 , 91 ) or inflammatory diseases such as Crohn's disease ( 92 , 93 ) or rheumatoid arthritis ( 94 , 95 ). Recently, nVNS has been proposed and applied to patients with respiratory symptoms of COVID-19 to modulate their inflammatory response ( 96 98 ). VNS improved cardiovascular parameters and decreased plasma and heart tissue biomarkers associated with heart failure in a canine model of heart failure ( 99 ) and lead to weight loss in dogs ( 100 ) and minipigs ( 101 ).…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%